Spatial distribution of Urban land-use in Addis Ababa, Ethiopia - Girmachew Tariku Jinollo; Liku Workalemahu; Dagnachew Adugna (Urban, Planning and Transport Research)
This study underlines the critical function of efficient urban land use planning, recommending mixed land use for improved city sustainability. The research, which is rooted in the historical context of urban renewal, attempts to harmonize theoretical frameworks with actual implementation, giving critical insights for policymakers and urban planners in constructing sustainable urban areas. The study identifies a deficit in empirical research on the spatial distribution of urban mixed land use, as well as a gap between theory and real application. Using a mixed-methods approach, it explores mixed land use planning concerns by including stakeholder input and temporal dynamics. Using theoretical frameworks, the study explores land use trends in four Addis Ababa sub-cities. When the null hypothesis of Complete Spatial Randomness is rejected, there is a significant relationship between location and land use functions (statistical chi-square value of 47.763). Finally, the study makes crucial recommendations for purposeful land use distribution in a dynamic urban setting, shedding light on the constraints of mixed land use planning in African urban growth.